Clean Village and Project Based Learning - Kulkarni, Milind (Journal of Engineering Education Transformations, 2016)
The industry complains that fresh Engineering graduates are not employable. They lack practical and hands on experience. ITM Group has four Engineering colleges located at Vizag, Nagpur, Raipur and Vadodara in India. The group has already introduced project based learning in all Engineering colleges. Many of these projects are executed in the campus. This concept will be now introduced at village level in the vicinity ofEngineeringColleges so that students will be exposed to broader level of experience. Students will gain practical technical knowledge, hands on experience, skills to work in a team, skills to interact with different stakeholders in society. Students will become employable and at the same time this will help in achieving the mission of clean village. There are different aspects of clean village such as: water supply, sanitation, indoor air quality, solid waste management etc. The paper discusses all these aspects with reference to Maharashtra State and India. This paper plans to propose a participatory role for Engineering College in the efforts of government to achieve themissions of clean village and skill development. This can be achieved by Project Based Learning in the identified areas.